Receptor-binding domain of MERS-CoV with optimal immunogen dosage and immunization interval protects human transgenic mice from MERS-CoV infection - Yufei Wang; Wanbo Tai; Jie Yang; Guangyu Zhao; Shihui Sun; Chien-Te K. Tseng; Shibo Jiang; Yusen Zhou; Lanying Du; Jimin Gao (Taylor & Francis Group, 2017)
Middle East respiratory syndrome (MERS) continues to raise worldwide concerns due to its pandemic potential. Increased MERS cases and no licensed MERS vaccines highlight the need to develop safe and effective vaccines against MERS. We have previously demonstrated that a receptor-binding domain (RBD) fragment containing residues 377-588 of MERS-coronavirus (MERS-CoV) spike protein is a critical neutralizing domain and an important vaccine target. Nevertheless, its optimal immunogen dosage and immunization interval, key factors for human-used vaccines that induce protective immunity, have never been investigated. In this study, we optimized these criteria using a recombinant MERS-CoV RBD protein fused with Fc (S377-588-Fc) and utilized the optimal immunization schedule to evaluate the protective efficacy of RBD against MERS-CoV infection in human dipeptidyl peptidase 4 transgenic (hDPP4-Tg) mice. Compared with one dose and 2 doses at 1-, 2-, and 3-week intervals, a regimen of 2 doses of this protein separated by an interval of 4 weeks induced the strongest antibody response and neutralizing antibodies against MERS-CoV infection, and maintained at a high level during the detection period. Notably, RBD protein at the optimal dosage and interval protected hDPP4-Tg mice against lethal MERS-CoV challenge, and the protection was positively correlated with serum neutralizing antibodies. Taken together, the optimal immunogen dosage and immunization interval identified in this study will provide useful guidelines for further development of MERS-CoV RBD-based vaccines for human use.